The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5603/fm.2015.0114
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of the mandibular lingula using cone-beam computed tomography

Abstract: (Folia Morphol 2015; 74, 4: 497-502)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
4
16
1
Order By: Relevance
“…The shape of the lingula has been found to vary across populations. 1 2 14 15 21 25 The distribution and the frequency of the shapes of the lingulae in this study were different from those reported in previous studies. The triangular shape was the most prevalent in the Indian population.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…The shape of the lingula has been found to vary across populations. 1 2 14 15 21 25 The distribution and the frequency of the shapes of the lingulae in this study were different from those reported in previous studies. The triangular shape was the most prevalent in the Indian population.…”
Section: Discussioncontrasting
confidence: 88%
“…The most common shape in this study was the nodular shape, which was also the most prevalent in the Turkish population. 2 21 The assimilated shape was the least prevalent in this study, as well as in most previous studies. 1 14 15 21 26 The identification of a lingula with a nodular or an assimilated pattern during maxillofacial surgery is often challenging, and thus accurate anatomical knowledge is imperative to prevent postoperative complications.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations